SOCIOLOGICAL REFLECTIONSON NEW HOUSING DEVELOPMENTS IN POST-SOCIALIST VILNIUS - Čiupailaitė, Dalia (Sociologija. Mintis ir veiksmas, 2012)
Planned housing developments are a new phenomenon in post-Soviet cities – cities marked since 1989 by the rapid and wholesale transformation of housing markets, from a situation of overwhelmingly state-owned provision to the development of real estate markets. In this article I explore how this type of dwelling transforms urban space, reflecting the new provisions in the period, but also revealing a dual relationship with socialist space. Planned housing developments are characterised by the continuity of the ‘soviet’, i.e. by modern functionalist urbanism’s architectural practices; but in their symbolic dimension such developments are also associated with an inversion of collective housing practices. This symbolic aspect of planned housing developments can be described in terms of privacy and sameness. In this article I argue that these housing practices are naturalised and affirmed as desirable through representations of space, including representations produced within marketing, mass media and the legal system. Drawing on the concepts of police, politics and the political developed by Rancière and Swyngedouw, the article raises the question of whether in post-socialist Vilnius these new developments indicate the consolidation of a post-political condition.Keywords: new housing developments, urban sociology, political.